Increased particle mass deposition on lung tissue due to industrial and waste-burning activities - Anusmita Das; Erwin W. Karg; George A. Ferron; Jürgen Schnelle-Kreis; Anil Kumar Mandariya; Gazala Habib; Alfred Wiedensohler; Mira L. Pöhlker; Ralf Zimmermann; Ajit Ahlawat (Environment International)
Understanding airborne particle mass deposition in the lungs is crucial for assessing health effects, particularly in regions with severe air pollution. While several studies have modelled lung deposition, there is limited information on lung tissue deposition that incorporates factors like hygroscopicity and density in polluted environments or source-specific exposures. This study examines the impact of atmospheric aerosol properties, including particle number size distribution, effective density, and hygroscopic growth, on lung tissue deposition using data from a measurement campaign in Delhi, India. Using the Hygroscopic Particle Lung Deposition (HPLD) model, the number (TDn) and mass (TDm) of tissue-deposited particles were calculated for various episodes: biomass burning (BB), chloride (Cl), hydrocarbon-like organic aerosol (HOA), and relatively clean (RC) periods. Chloride episodes, linked to industrial and waste burning activities, showed the highest tissue deposition mass (28 pg cm−2h−1), followed by BB (22 pg cm−2h−1), HOA (17 pg cm−2h−1), and RC (14 pg cm−2h−1) on total inner lung surface area. In addition, incorporating hygroscopicity and density increased deposition estimates by 1.8–2.8 times. This study underscores the importance of quantifying tissue deposition doses for improving exposure assessments, particularly in highly polluted regions where elevated particulate levels exacerbate lung inflammation, respiratory issues, and cancer risk.